HIGH PERFORMANCE THIN LAYER CHROMATOGRAPHIC DETERMINATION OF CAFFEIC ACID AND ROSMARINIC ACID FROM THE LEAVES OF Orthosiphon stamineus - M. Amzad Hossain; Zhari Ismail (Indonesian Journal of Chemistry, 2009)
This paper presents the studies performed on extraction of Orthosiphon stamineus, Benth by using different solvent for the identification and quantification of the caffeic acid derivatives such as caffeic acid  and rosmarinic acid which confers to the leaves of this plant with remarkable pharmaceutical properties. High performance thin-layer chromatographic (HPTLC) allows the identification and the quantification of more than 20 samples in the same chromatographic run. The analysis of the samples requires 15-30 min compared with more than 2 h using a typical HPLC method. Using the techniques of the HPTLC and the UV-VIS spectra we have found that the extraction of this herb plant contain, the caffeic acid and rosmarinic acid ranging between 0.029% up to 0.506% and up to 0.24% to 2.24% respectively.